Moken Ethnic Groups: The Marginalization and Construction of Social Space under Thai Nation – State - Changkid, Pariwat; Chaisingkananont, Somrak (Journal of Liberal Arts Prince of Songkla University, 2019)
This article aimed to explain the construction of social space of the Moken ethnic groups in Koh Lao, Koh Chang and Koh Phayam, Ranong province of Thailand. Using field research Method, data were collected by observations and in-depth interviews with 15 persons of Moken ethnic groups, 5 related persons and document research. The data were classified according to the issues, decoded, interpreted and presented by means of description. It was found that although the Moken ethnic groups were marginalized, they did not accept that status and attempted to get Thai citizenship in various ways through everyday life. This article reflects that, Most moken ethnic groups are not recognized as both legal and social citizens. They have no access to public services, thus creating a social space to get more recognition.